2021
DOI: 10.1126/scitranslmed.abi7643
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light protein correlates with unfavorable clinical outcomes in hospitalized patients with COVID-19

Abstract: Brain imaging studies of patients with COVID-19 show evidence of macro- and micro-hemorrhagic lesions, multifocal white matter hyperintensities, and lesions consistent with posterior reversible leukoencephalopathy. Imaging studies, however, are subject to selection bias and prospective studies are challenging to scale. Here, we evaluated whether serum neurofilament light chain (NFL), a neuroa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 38 publications
9
98
1
Order By: Relevance
“…For patients with moderatelyto-severely elevated anxiety and depression symptoms, referral for psychiatric evaluation should also be considered. Finally, the detection of focal neurocognitive deficits may warrant further neurological work-up to assess for structural contributors to dysfunction (e.g., neuroimaging to assess for stroke), biofluid markers of inflammation (e.g., cerebrospinal fluid assessment for leukocytosis, or serum measures of neurofilament light [32], or other issues (e.g., polysomnography to assess for occult sleep dysfunction), which may influence long-term prognosis or benefit from specific treatment (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with moderatelyto-severely elevated anxiety and depression symptoms, referral for psychiatric evaluation should also be considered. Finally, the detection of focal neurocognitive deficits may warrant further neurological work-up to assess for structural contributors to dysfunction (e.g., neuroimaging to assess for stroke), biofluid markers of inflammation (e.g., cerebrospinal fluid assessment for leukocytosis, or serum measures of neurofilament light [32], or other issues (e.g., polysomnography to assess for occult sleep dysfunction), which may influence long-term prognosis or benefit from specific treatment (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…sNFL is an easily accessible age-dependent biomarker, commonly used to screen for disease severity and/or progression in several pathologies related to neuronal loss. NFL has also been detected in the CSF of critically ill 4 and the serum of hospitalized individuals 5 with COVID-19. This study demonstrated a positive correlation of sNFL with worse clinical outcomes and COVID-19 severity.…”
Section: Main Textmentioning
confidence: 97%
“…Some authors have found that patients with COVID-19 admitted to the ICU show elevated levels of glial fibrillary acidic protein and neurofilament light protein (NfL) in the blood, ( 44 , 45 ) and that high NfL levels are associated with poorer prognosis. ( 44 , 46 , 47 ) A recent study including 142 hospitalised patients found that even patients with no neurological symptoms presented high NfL levels, and that high levels were associated with poor outcomes. ( 47 ) Another study reported elevated plasma levels of IL-4 and markers of neuronal damage in neuronal-enriched extracellular vesicles in patients with neurological symptoms.…”
Section: Correlation Between Cognitive Symptoms and Biomarkersmentioning
confidence: 99%
“…( 44 , 46 , 47 ) A recent study including 142 hospitalised patients found that even patients with no neurological symptoms presented high NfL levels, and that high levels were associated with poor outcomes. ( 47 ) Another study reported elevated plasma levels of IL-4 and markers of neuronal damage in neuronal-enriched extracellular vesicles in patients with neurological symptoms. ( 48 ) However, few studies have analysed biomarkers in patients undergoing cognitive assessment.…”
Section: Correlation Between Cognitive Symptoms and Biomarkersmentioning
confidence: 99%